A global perspective on cervical cancer screening: a literature review - Rauf, Lubna; Eid, Ahmed; Hamed, Ehab (International Journal Of Community Medicine And Public Health, 2023)
Cervical cancer is a significant health issue for women globally, with over 600,000 new cases and 342,000 deaths in 2020. Effective cervical screening programs, including primary screening methods such as Pap tests, human papillomaviruses (HPV) deoxyribonucleic acid (DNA) testing, and liquid-based cytology, can prevent and detect early cancer cases, improving morbidity and mortality rates. However, screening uptake varies widely across countries, with high-income countries have achieved over 70% uptake but low- and middle-income countries lagging due to a lack of recommendations and centralised screening systems. Even in high-income countries in the Middle East, uptake remains low, requiring further investigation. This review explores barriers to screening programme delivery and highlights centralised and multi-level interventions that have proven effective worldwide. Future research should focus on culturally sensitive approaches, healthcare infrastructure strengthening, and community education and outreach programs to address uptake disparities and barriers.